INDONESIAN MUSLIM WOMEN IN CONTEMPORARY POLITICAL CONTESTATIONS: Challenges to Gender Mainstreaming Policy in The 2019 Elections - Bani Syarif Maula (AL-TAHRIR, 2019)
Abstract: Achieving equal opportunities between women and men in political competition has always been a complex process, even though the government has established affirmative policies to encourage a greater role for women in the political sphere. The issue of patriarchal culture and the challenge of religious conservatism can hamper the achievement of the objectives of the affirmation policy for women in competing for elections to occupy the position of parliament members (DPR-RI). This paper discusses the political contestation of women in reaching political positions as people's representatives and the challenges they face in fighting for issues of gender equality in the parliament. This research answers what factors are hampering women's involvement in political contestation, and what challenges are there in fighting for gender equality issues. This study used a qualitative method with a descriptive analysis approach. The theory used in this study was the concept of affirmative action and the theory of gender equality in politics. The results of the discussion showed that the number of women elected in the 2019 Elections increased. Thanks to the affirmative policy ruled by the Indonesian government. However, affirmative policies to meet gender quotas do not only benefit those who have gender equality agendas, but also those who stand with the anti-feminist movement that represents the voices of conservative groups. The issue they are fighting for is still trapped in the gender ideology proclaimed by a patriarchal culture, which assumes women's problems are identical to those of mothers. Therefore, not all elected women MPs explicitly have a gender perspective. الملخص:إن تحقيق تكافؤ الفرص بين النساء والرجال في المنافسة السياسية كان دائمًا عملية معقدة ، على الرغم من أن الدولة وضعت سياسات إيجابية لتشجيع دور أكبر للمرأة في المجال السياسي.يمكن أن تعوق مسألة الثقافة الأبوية وتحدي المحافظة الدينية تحقيق أهداف سياسة التأكيد للمرأة في التنافس على الانتخابات لشغل منصب أعضاء البرلمان (مجلس النواب لجمهورية إندونيسيا). تناقش هذه الورقة التنافس السياسي للمرأة في الوصول إلى المناصب السياسية كممثلة للشعب والتحديات التي تواجهها في الكفاح من أجل قضايا المساواة بين الجنسين في البرلمان.يجيب هذا البحث عن العوامل التي تعوق مشاركة المرأة في التنافس السياسي ، والتحديات التي تواجهها النساء في الكفاح من أجل قضايا المساواة بين الجنسين. تستخدم هذه الدراسة طريقة نوعية مع نهج التحليل الوصفي.النظرية المستخدمة في هذه الدراسة هي مفهوم العمل الإيجابي ونظرية المساواة بين الجنسين في السياسة. تظهر نتائج البحث أن عدد النساء المنتخبات في انتخابات 2019 زاد بنسبة 22 في المائة. بفضل السياسة الايجابية التي تحكمها الحكومة الاندونيسية.ومع ذلك ، فإن السياسات الإيجابية للوفاء بحصص النوع الاجتماعي لا تفيد فقط أولئك الذين لديهم أجندة للمساواة بين الجنسين ، ولكن أيضًا أولئك الذين يقفون إلى جانب الحركة المناهضة للنسوية التي تمثل أصوات الجماعات المحافظة.إن القضية التي يناضلون من أجلها لا تزال عالقة في الأيديولوجية الجنسانية التي أعلنتها ثقافة أبوية ، والتي تفترض أن مشاكل المرأة مماثلة لمشاكل الأمهات.لذلك ، لم يكن لجميع البرلمانيات المنتخبات منظور جنساني بشكل واضح.Abstrak: Mencapai peluang yang setara antara perempuan dan laki-laki dalam persaingan politik selalu menjadi proses yang kompleks, meskipun negara telah menetapkan kebijakan afirmatif untuk mendorong peran yang lebih besar bagi perempuan dalam ranah politik. Persoalan budaya patriarkal dan tantangan konservatisme agama dapat menghambat pencapaian tujuan kebijakan afirmasi bagi perempuan dalam memperebutkan pemilihan untuk menduduki posisi anggota DPR-RI. Kajian ini membahas kontestasi politik perempuan dalam mencapai posisi sebagai wakil rakyat dan tantangan yang mereka hadapi dalam memperjuangkan isu-isu kesetaraan gender di parlemen. Penelitian ini menjawab faktor-faktor apa yang menghambat keterlibatan perempuan dalam kontestasi politik, dan tantangan apa yang dihadapi perempuan dalam memperjuangkan isu kesetaraan gender. Penelitian ini menggunakan metode kualitatif dengan pendekatan analisis deskriptif. Teori yang digunakan dalam penelitian ini adalah konsep affirmative action dan teori kesetaraan gender dalam politik. Hasil kajian menunjukkan bahwa jumlah perempuan yang terpilih dalam Pemilu 2019 meningkat 22 persen berkat kebijakan afirmatif yang ditetapkan oleh pemerintah. Namun demikian, kebijakan afirmatif untuk memenuhi kuota perempuan tidak hanya menguntungkan mereka yang memiliki agenda kesetaraan gender, tetapi juga mereka yang mendukung gerakan anti-feminis yang mewakili suara-suara kelompok konservatif. Masalah yang mereka perjuangkan masih terjebak dalam ideologi gender yang diproklamasikan oleh budaya patriarki, yang menganggap masalah perempuan identik dengan masalah ibu. Karena itu, tidak semua anggota parlemen perempuan yang terpilih secara eksplisit memiliki perspektif gender.